Essential Oils as an Intervention Strategy to Reduce Campylobacter in Poultry Production: A Review - Micciche, Andrew; Rothrock, Michael J.; Yang, Yichao; Ricke, Steven C. (Frontiers in Microbiology, 2019)
Campylobacter is a major foodborne pathogen and can be acquired through consumption of poultry products. With 1.3 million U.S. cases a year, the high prevalence of Campylobacter within the poultry gastrointestinal tract is a public health concern and thus a target for the development of intervention strategies. Increasing demand for antibiotic-free products has led to the promotion of various alternative pathogen control measures both at the farm and processing level. One such measure includes utilizing essential oils in both pre- and post-harvest settings. Essential oils are derived from plant-based extracts, and there are currently over 300 commercially available compounds. They have been proposed to control Campylobacter in the gastrointestinal tract of broilers. When used in concentrations low enough to not influence sensory characteristics, essential oils have also been proposed to decrease bacterial contamination of the poultry product during processing. This review explores the use of essential oils, particularly thymol, carvacrol, and cinnamaldehyde, and their role in reducing Campylobacter concentrations both pre- and post-harvest. This review also details the suggested mechanisms of action of essential oils on Campylobacter.